Pronunciation of Dialects and Accents - Lubis, Yani; Ibriza, Tazkiya Aulia; Hakim BB, Agung Arif; Siregar, Amanda; Husna, Nurul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Accents and dialects are important aspects of linguistic studies that reflect the diversity of languages around the world. Accent refers to the distinctive way a person or group pronounces words, which can be influenced by geographical, social and cultural factors. For example, the Southern American English accent has distinctive features in its pronunciation and intonation that set it apart from other accents in the United States. Dialects, on the other hand, encompass a wider variety of language, including different vocabulary, syntax, and grammatical conventions. Understanding accents and dialects is important because it facilitates better communication between native and non-native speakers of a language. It also helps us appreciate the cultural richness contained in the language, as well as understand the identity and social affiliation expressed through the way a person speaks. In this era of globalization, a better understanding of accents and dialects also supports deeper cultural integration in international communication and cooperation across countries. As such, the study of accent and dialect involves not only linguistic analysis but also an exploration of the cultural and social role of language in society. This provides a deep insight into the complexity of human communication and relationships around the world.